Mastıcatory Muscle Actıvıty And Cranıofacıal Form Relatıonshıp In Anterıor Open Bıte Patıents - Sevil Akkaya (Galenos Yayinevi, 1995)
In this stduy 10 patients with skeletal and dental open bite were compared with another 10 patients with normal occlusion according to their dental, skeletal parameters and muscle activity. There was statistically significant differences in dental and skeletal parameters between the two groups and masticatory muscle activities tended to be smaller in open bite group when compared to normal occlusion group.